Economy is not a barometer of the age of woman's first marriage - Rafly Parenta Bano; Muhammad Saifudin; Anthonia Karolina Rejo Lobwaer (EKONOMI & SOSIAL, 2020)
One of the most interesting topics in studies related to women, family to marriage is the issue of the age of first marriage for women. This study aims to determine the social, economic and demographic factors on the age at first marriage of women in Indonesia. Cox proportional hazard regression analysis was applied to the results data. The results indicate that singulate mean age at marriage (SMAM) and the average age at first marriage for women in Indonesia are around 23.42 years and 19.52 years, respectively. The results of both bivariate and multivariate statistical analysis show that all independent variables significantly determine the time of women's first marriage in Indonesia. The variables level of education, residence and female birth cohort are the most significant variables in the model. This study found that women from the youngest generation (gene Z) had a higher likelihood of marrying earlier than women from the previous generation. Overall, it was found that there was a shift in the factor at determinant age the first marriage of women, where education was the barometer, so that more vigorous efforts are needed to keep Indonesian women in school for a long time, in this case, girls who come from economically disadvantaged households should be given a full free scholarship up to the level of undergraduate education.